Acompañamiento como pasante en la ejecución de proyectos civiles en la Empresa Incordis S.A.S Duitama, Boyacá (2023)
By carrying out the internship at the company Incordis S.A.S, in the Municipality of Duitama - Boyacá, the aim was to reinforce and put into practice the knowledge acquired in the classroom, based on real situations such as work under pressure, workload management and conflict resolution, seeking the development of high-level capabilities and competencies in the exercise of civil engineering, in order to obtain positive results that allowed the population with whom we interacted to benefit through honesty and good development. of professional ethics. Likewise, the intervention of the student intern in a company like Incordis S.A.S allowed him to acquire initial work experience, regarding the preparation of budgets, construction design, activity execution reports and all those assigned by the supervisor, which were structured within this informative article, to publicize professional training and its successful performance in future jobs, in which their knowledge, skills, abilities and human values must be demonstrated to correctly carry out the work and be able to provide a guarantee of quality, and effectiveness in all the processes it is part of.